Pengaruh Bias Heuristik terhadap Keputusan Investasi Saham melalui Mediasi Persepsi Risiko - Herry Syahputra; Febri Nila Chrisanty (CV. ITTC INDONESIA, 2026)
The increasing number of young investors in Indonesia in recent years reflects significant growth in capital market participation. However, this phenomenon also raises the potential for investment decisions influenced by psychological factors, particularly heuristic biases and risk perception. This study aims to analyze the effect of overconfidence, representativeness, availability, gambler’s fallacy, and anchoring on stock investment decisions, as well as to examine the role of risk perception as a mediating variable among young retail investors in Tangerang City.This research employs a quantitative approach with a causal research design and a cross-sectional method. The population consists of young retail investors aged 18–35 years who have been actively investing in stocks for at least one year. A total of 188 respondents were selected using purposive sampling. Primary data were collected through a five-point Likert scale questionnaire and analyzed using Structural Equation Modeling–Partial Least Squares (SEM-PLS).The results indicate that all heuristic bias variables have a positive effect on investment decisions. Furthermore, risk perception significantly influences investment decisions and serves as a mediating variable, with a negative mediating effect on the relationship between availability bias and investment decisions. These findings confirm that young investors’ decisions are not entirely rational but are influenced by cognitive biases and risk perception. Therefore, enhancing behavioral financial literacy is essential to promote wiser and more sustainable investment decision-making.